Effect of fragmented Lactobacillus amylovorus CP1563 on lipid metabolism in overweight and mildly obese individuals: a randomized controlled trial. (1st January 2016) - Nakamura, Futoshi; Ishida, Yu; Aihara, Kohtaro; Sawada, Daisuke; Ashida, Nobuhisa; Sugawara, Tomonori; Aoki, Yumeko; Takehara, Isao; Takano, Kazuhiko; Fujiwara, Shigeru
Abstract : Background: Previously, we showed that fragmented Lactobacillus amylovorus CP1563 (CP1563) functions as a dual agonist of peroxisome proliferator-activated receptor α and γ in vitro and in vivo . Objective: Here, we examined the safety and effect of CP1563 ingestion on body fat in obese class I participants in a double-blinded, placebo-controlled, randomized clinical trial (RCT). Design: In the RCT, 200 participants with a body mass index (BMI) of 25–30 kg/m 2 consumed test beverages with or without 200 mg of CP1563 daily for 12 weeks. In total, 197 subjects completed the study without any adverse effects. Results: Body fat percentage, whole body fat, and visceral fat were significantly decreased in the test group compared with the placebo group ( p< 0.001, p< 0.001, and p< 0.001, respectively). Triglycerides, total cholesterol, LDL-cholesterol, and diastolic blood pressure showed significant reductions in the test group compared with the placebo group ( p< 0.001, p< 0.001, p< 0.001, and p< 0.001, respectively). Additionally, significant differences in the changes in blood glucose, insulin, homeostasis model assessment-insulin resistance (HOMA-IR), and uric acid were observed between the two groups ( p< 0.001, p= 0.004, p< 0.001, and p< 0.001, respectively). Improvements in anthropometric measurements and markers were observed in obese class I subjects in the test group. Conclusions: Daily consumption of beverages containing fragmented CP1563 for 12 weeks by obese class I subjects improved anthropometric measurements and markers related to lipid and glucose metabolism without any adverse effects. These results suggest that the consumption of foods containing fragmented CP1563 reduces body fat and prevents metabolic syndrome.